Resistance training voluntary to failure effects to muscle thickness and strength in overweight women / Puteri Nur Aida Ismail ... [et al.] - Ismail, Puteri Nur Aida; Aqilah Shafee, Siti Syahirah; Ismail, Zulkifli; Mohamed Roseli, Mohd Irzat Rozaidy; Gray, Stuart; Ismail, Ahmad Dzulkarnain (Universiti Teknologi MARA, Perlis, 2024)
Skeletal muscle has an often-underappreciated role in health, with low muscle strength being linked with increased risk of a range of poor health outcomes. It has been demonstrated recently that if exercise is performed voluntarily to failure, then gains in muscle mass and strength are similar regardless of the load at which exercise is performed. The aim of this study was to compare the effect of resistance training voluntary to failure on muscle thickness and strength in overweight women. Twelve overweight women (age 31 ± 8years; height 157.7 ± 4.7cm; weight 71.9 ± 8.9kg; body mass index 28.9 ± 3.2 kg m²) were recruited to the study. Resistance training involved three sessions per week for 6 weeks. Each session involved one set of nine exercises, performed at 80% of one-repetition maximum voluntary to failure. Session lasted 15-20 min. Muscle thickness (ultrasound) and muscle strength were measured at baseline and post – intervention. Resistance training resulted in a 5.2 ± 4.6% (P < 0.05) increased in muscle thickness and 31.0 ± 8.2% (P < 0.05) increased in muscle strength than baseline, respectively. Six weeks of resistance training three session per week with 20 minutes per session voluntary to failure at 80% of 1RM increases in muscle thickness and strength in overweight women.